CNTs synthesized with polyoxometalate-based metal–organic compounds as catalyst precursors via the CVD method and their adsorption performance towards organic dyes. (26th March 2020) - Tian, Yuan; Wang, Xiu-Li; Luan, Jian; Lin, Hong-Yan; Chang, Zhi-Han; Wang, Xiang; Liu, Guo-Cheng
Abstract : CNTs were synthesized with POM-based compounds as catalyst precursors via the CVD method, and they possess a high adsorption capacity towards organic dyes. Abstract : Successful production of carbon nanotubes (CNTs) was achieved via chemical vapor deposition (CVD) with the following four new polyoxometalate (POM)-based metal–organic compounds (MOCs) as catalyst precursors: (4-H2 bptzb)2 [HPMo12 O40 ]2 ·H2 O (1 ), Ag(4-H2 bptzb)(H2 O)[PMo12 O40 ] (2 ), Ag3 (3-bptzb)2 [PMo12 O40 ] (3 ), and Ag4 (3-bptzpe)3 (H2 O)2 [HPMo12 O40 ]2 (4 ) (3-bptzb = 1, 4-bis(5-(3-pyridyl)tetrazolyl)-propane, 4-bptzb = 1, 4-bis(5-(4-pyridyl)tetrazolyl)-propane, and 3-bptzpe = 1, 4-bis(5-(3-pyridyl)tetrazolyl)-pentane). The Mo2 C nanoparticles transformed from the POM-based MOCs 1–4 acted as catalysts for the synthesis of CNTs 1–4. The different specific surface areas of CNTs 1–4 can be attributed to the content of Mo2 C nanoparticles, which may be due to the diverse components and structures of compounds 1–4 . The as-grown CNTs exhibit a high adsorption activity towards the organic dyes methylene blue (MB), safranine T (ST) and methylene orange (MO).